Maqasid ash-Syariah Approach to Jarimah Al-Riddah - Imamuddin Imamuddin; Raja Siahaan (AT-TAFAHUM: Journal of Law, 2022)
The research method used is qualitative with a normative juridical approach through literature study. Data were obtained from Islamic legal sources such as the Qur'an, hadith, and relevant classical and modern fiqh literature. Data analysis techniques were carried out descriptively and analytically by examining the concept of jarimah al-riddah and linking it to the principles of maqashid sharia, such as hifz al-din, hifz al-nafs, and hifz al-'aql. The results of the study indicate that the maqashid sharia approach provides a more comprehensive and contextual understanding of jarimah al-riddah. It is not only understood as a violation of religion, but must also consider the protection of human rights, freedom of belief, and the public interest. Therefore, a wise and proportional interpretation is needed so that the application of the law remains in line with the main objectives of sharia, namely realizing justice and avoiding harm.